A Method for Performing Reforestation to Effectively Recover Soil Water Content in Extremely Degraded Tropical Rain Forests - Liu, Tiedong; Jiang, Kai; Tan, Zhaoyuan; He, Qifang; Zhang, Hui; Wang, Chen (Frontiers in Ecology and Evolution, 2021)
Deforestation continues to be extensive in the tropics, resulting in reduced soil water content. Reforestation is an effective way to recover soil water content, but the recovery depends on the type of reforestation efforts that are implemented. Monoculture of fast-growing species is a common reforestation strategy, because it is an effective means of preventing landslides resulting from the frequent typhoons and heavy rains in the tropics and easy to implement. To quantify whether monoculture plantings can help recover soil water content, we initiated a reforestation project within a 0.2 km2 area of an extremely degraded tropical monsoon forest. We hypothesized that much higher transpiration rate of fast-growing tree species would deplete soil water more than the dominant slow-growing species in the adjacent secondary tropical rain forest during both wet and dry seasons, thereby resulting in much lower soil water content. To test this hypothesis, we compared transpiration rates and key functional traits that can distinguish transpiration rates between fast-growing and dominant slow-growing species in both wet and dry seasons. We also quantified whether soil water content around these species differed. We found that fast-growing species had transpiration rate and transpiration-related trait values that were 5-10 times greater than the dominant slow-growing species in both seasons. We also found that soil water content around dominant slow-growing species was 1.5-3 times greater than for fast-growing species in both seasons. Therefore, reforestation based on monoculture plantings of fast-growing species seems difficult to effectively recover the soil water content. We also provide a simple method for guiding the use of reforestation efforts to recover soil water content in extremely degraded tropical rain forests. We expect that this simple method can be an effective means to restore extremely degraded tropical rain forests in other parts of the world.